N, S co-doped hollow carbon spheres, and preparation method and application thereof

By using N and S co-doped hollow carbon balls as the positive electrode material of aluminum ion capacitors, the problem of limited improvement in electrochemical performance of aluminum ion capacitors is solved, and the conductivity and ion adsorption/desorption performance are improved, thereby improving electricity Chemical properties.

CN119409169APending Publication Date: 2025-02-11广东格林赛福能源科技有限公司 +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411584651.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The electrochemical performance improvement of aluminum ion capacitors is affected by the damage to the material structure and the difficulty of ion insertion/exit.

Method used

Using N and S co-doped hollow carbon spheres as the positive electrode material, the preparation method includes preparation of mixed solutions, hydrothermal reaction and high temperature carbonization, and other steps to form N and S co-doped hollow carbon with high conductivity and large specific surface area. ball.

Benefits of technology

Improve the conductivity and ion adsorption/desorption performance of N and S co-doped hollow carbon spheres, increase the contact area between the electrode material and the electrolyte, promote ion transport, and greatly improve the electrochemical performance of aluminum ion capacitors. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409169A_ABST
    Figure CN119409169A_ABST
Patent Text Reader

Abstract

The invention relates to N, S co-doped hollow carbon spheres, and a preparation method and application thereof. The method comprises the following steps: S1, uniformly mixing ethanol, ammonia water and deionized water; s2, sequentially adding tetraethoxysilane, resorcinol, formaldehyde, thiourea and F127 (polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer), and uniformly mixing the tetraethoxysilane, the resorcinol, the formaldehyde, the thiourea and the F127 (polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer); s3, adding ethyl orthosilicate again, and stirring overnight to obtain a mixed solution; s4, pouring the mixed solution into a reaction kettle for hydrothermal reaction to obtain an N, S co-doped hollow carbon sphere precursor; and S5, placing the N and S co-doped hollow carbon sphere precursor in inert gas, performing high-temperature carbonization, and then placing the carbonized product in a potassium hydroxide aqueous solution for soaking until SiO2 is completely removed to obtain the N and S co-doped hollow carbon sphere. The N, S co-doped hollow carbon sphere prepared by the method is used as a positive electrode material to be applied to an aluminum ion capacitor, and the electrochemical performance of the aluminum ion capacitor can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum ion capacitors, and in particular to a N and S co-doped hollow carbon sphere, a preparation method and application thereof. Background Art

[0002] As a new type of electrochemical energy storage device with high energy density, high power density and long cycle life, ion capacitors show great market prospects.

[0003] Relative to monovalent and divalent metal ions (Li + , Na + , K + ,Mg 2+ , Zn 2+ and Ca 2+ ), trivalent Al 3+ It has the advantages of abundant resources, high charge density and high specific capacity for electrochemical energy storage, and is expected to become an ideal choice for large-scale energy storage systems. However, since aluminum ions carry three positive charges, the strong interaction between them and the positive electrode material may cause damage to the material structure and affect the insertion and extraction of ions, which limits the improvement of the electrochemical performance of aluminum ion capacitors. Therefore, it is necessary to develop a positive electrode material that can improve the electrochemical performance of aluminum ion capacitors. Summary of the invention

[0004] Based on this, it is necessary to provide a N, S co-doped hollow carbon sphere, a preparation method and application thereof to address the problem that the improvement of the electrochemical performance of existing aluminum ion capacitors is limited.

[0005] A method for preparing N and S co-doped hollow carbon spheres comprises the following steps:

[0006] S1. Evenly mix ethanol, ammonia water and deionized water to obtain a mixed solution A;

[0007] S2, adding tetraethyl orthosilicate, resorcinol, formaldehyde, thiourea and F127 to the mixed solution A prepared in S1 in sequence and mixing evenly to obtain a mixed solution B;

[0008] S3, adding ethyl orthosilicate to the mixed solution B prepared in S2, stirring overnight to obtain a mixed solution C;

[0009] S4, pouring the mixed solution C prepared in S3 into a reactor for hydrothermal reaction to obtain a N, S co-doped hollow carbon sphere precursor;

[0010] S5, placing the N, S co-doped hollow carbon sphere precursor prepared by S4 in an inert gas, carbonizing it at high temperature, and then soaking the N, S co-doped hollow carbon sphere precursor after high temperature carbonization in a potassium hydroxide aqueous solution until SiO is completely removed. 2 , and N, S co-doped hollow carbon spheres were obtained.

[0011] As a preferred solution, the volumes of the ethanol, the ammonia water and the deionized water in S1 are all 0 to 50 mL.

[0012] As a preferred solution, the volumes of the ethyl orthosilicate and the formaldehyde in S2 are both 0-10 mL.

[0013] As a preferred solution, the masses of the resorcinol, the thiourea and the F127 in S2 are all 0-5 g.

[0014] As a preferred embodiment, the F127 is a polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer.

[0015] As a preferred solution, the volume of the tetraethyl orthosilicate in S3 is 0 to 10 mL.

[0016] As a preferred solution, the temperature required in the hydrothermal reaction process in S4 is 60°C to 300°C.

[0017] As a preferred solution, the temperature of the high temperature carbonization in S5 is 400°C to 1200°C.

[0018] As a preferred embodiment, the concentration of the potassium hydroxide aqueous solution in S5 is 1 mol L -1 .

[0019] A N, S co-doped hollow carbon sphere prepared by the preparation method as described above.

[0020] The N, S co-doped hollow carbon spheres prepared by the preparation method described above are used as positive electrode materials in aluminum ion capacitors.

[0021] The beneficial effects of the present invention are as follows: the conductivity and ion adsorption / desorption performance of N, S co-doped hollow carbon spheres are improved by element doping; the structure of the hollow carbon spheres can make the N, S co-doped hollow carbon spheres have a larger specific surface area, which is beneficial to increase the contact area between the electrode material and the electrolyte, is beneficial to ion transmission, and greatly improves the electrochemical performance of the aluminum ion capacitor. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope image of the N and S co-doped hollow carbon spheres prepared in Example 1 of the present invention;

[0023] Figure 2The cyclic voltammetry curve of the aluminum ion capacitor using N and S co-doped hollow carbon spheres as positive electrode materials prepared in Example 1 of the present invention;

[0024] Figure 3 The cycle performance curve of the aluminum ion capacitor using N and S co-doped hollow carbon spheres as positive electrode materials prepared in Example 1 of the present invention;

[0025] Figure 4 This is a rate performance curve of the aluminum ion capacitor using N and S co-doped hollow carbon spheres as positive electrode materials prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0027] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0028] Example 1

[0029] Preparation of N, S co-doped hollow carbon spheres

[0030] S1. Pour 35 mL of ethanol, 1.5 mL of ammonia water and 5 mL of deionized water into a beaker and stir until the mixture is uniform and stable to obtain a mixed solution A.

[0031] S2, 1.4 mL of tetraethyl orthosilicate, 0.2 g of resorcinol, 0.28 mL of formaldehyde, 0.2 g of thiourea and 90 mg of F127 were added to the mixed solution A prepared in S1, and stirred until completely dissolved to prepare a mixed solution B;

[0032] S3, adding 0.75 mL of ethyl orthosilicate to the mixed solution B prepared in S2 again, stirring overnight to prepare a mixed solution C;

[0033] S4, pouring the mixed solution C prepared in S3 into a reaction kettle, and hydrothermally treating at 100° C. for 24 hours to obtain a hollow N, S co-doped carbon sphere precursor;

[0034] S5, the N, S co-doped hollow carbon sphere precursor prepared by S4 was carbonized at 800 °C for 2 hours under argon conditions, and then the carbonized N, S co-doped hollow carbon sphere precursor was immersed in a 1 mol L -1 of potassium hydroxide aqueous solution until the SiO 2 , and N, S co-doped hollow carbon spheres were obtained.

[0035] Example 2

[0036] Preparation of N, S co-doped hollow carbon spheres

[0037] S1. Pour 50 mL of ethanol, 10 mL of ammonia water and 50 mL of deionized water into a beaker and stir until the mixture is uniform and stable to obtain a mixed solution A.

[0038] S2, 10 mL of tetraethyl orthosilicate, 0.6 g of resorcinol, 0.8 mL of formaldehyde, 5 g of thiourea and 3 g of F127 were added to the mixed solution A prepared in S1, and stirred until completely dissolved to prepare a mixed solution B;

[0039] S3, adding 5 mL of ethyl orthosilicate to the mixed solution B prepared in S2, stirring overnight to prepare a mixed solution C;

[0040] S4, pouring the mixed solution C prepared in S3 into a reaction kettle, and hydrothermally treating at a temperature of 150° C. for 24 hours to obtain a hollow N, S co-doped carbon sphere precursor;

[0041] S5, the N, S co-doped hollow carbon sphere precursor prepared by S4 was carbonized at a constant temperature of 400 ° C for 4 hours under argon conditions, and then the carbonized N, S co-doped hollow carbon sphere precursor was immersed in a 1 mol L -1 of potassium hydroxide aqueous solution until the SiO 2 , and N, S co-doped hollow carbon spheres were obtained.

[0042] Example 3

[0043] Preparation of N, S co-doped hollow carbon spheres

[0044] S1. Pour 25 mL of ethanol, 8 mL of ammonia water and 50 mL of deionized water into a beaker and stir until the mixture is uniform and stable to obtain a mixed solution A.

[0045] S2, 5 mL of tetraethyl orthosilicate, 0.5 g of resorcinol, 0.8 mL of formaldehyde, 2 g of thiourea and 5 g of F127 were added to the mixed solution A prepared in S1, and stirred until completely dissolved to prepare a mixed solution B;

[0046] S3, adding 10 mL of ethyl orthosilicate to the mixed solution B prepared in S2, stirring overnight to prepare a mixed solution C;

[0047] S4, pouring the mixed solution C prepared in S3 into a reaction kettle, and hydrothermally treating at 60° C. for 36 hours to obtain a hollow N, S co-doped carbon sphere precursor;

[0048] S5, the N, S co-doped hollow carbon sphere precursor prepared by S4 was carbonized at 900 °C for 1 hour under argon gas, and then the carbonized N, S co-doped hollow carbon sphere precursor was immersed in a 1 mol L -1 of potassium hydroxide aqueous solution until the SiO 2 , and N, S co-doped hollow carbon spheres were obtained.

[0049] Example 4

[0050] Preparation of N, S co-doped hollow carbon spheres

[0051] S1. Pour 50 mL of ethanol, 20 mL of ammonia water and 50 mL of deionized water into a beaker and stir until the mixture is uniform and stable to obtain a mixed solution A.

[0052] S2, to the mixed solution A prepared in S1, 10 mL of tetraethyl orthosilicate, 5 g of resorcinol, 10 mL of formaldehyde, 5 g of thiourea and 5 g of F127 were added in sequence, and stirred until completely dissolved to prepare a mixed solution B;

[0053] S3, adding 10 mL of ethyl orthosilicate to the mixed solution B prepared in S2, stirring overnight to prepare a mixed solution C;

[0054] S4, pouring the mixed solution C prepared in S3 into a reaction kettle, and hydrothermally treating at 300° C. for 12 hours to obtain a hollow N, S co-doped carbon sphere precursor;

[0055] S5, the N, S co-doped hollow carbon sphere precursor prepared by S4 was carbonized at a constant temperature of 1200 ° C for 2 hours under argon conditions, and then the carbonized N, S co-doped hollow carbon sphere precursor was immersed in a 1 mol L -1 of potassium hydroxide aqueous solution until the SiO 2 , and N, S co-doped hollow carbon spheres were obtained.

[0056] Test Example 1

[0057] Scanning electron microscope test

[0058] Test method: Scanning electron microscope was used to scan the N and S co-doped hollow carbon spheres prepared in Example 1. Figure 1shown.

[0059] Depend on Figure 1 It can be seen that the N and S co-doped hollow carbon spheres have a hollow spherical structure, and the large effective specific surface area is conducive to the full contact between the electrolyte and the electrode material. The large specific surface area is conducive to the adsorption / desorption of more ions.

[0060] Test Example 2

[0061] Cyclic voltammetry test

[0062] Test method:

[0063] 1) The N and S co-doped hollow carbon spheres prepared in Example 1 were used as positive electrodes and assembled with commercially available aluminum negative electrodes into aluminum ion capacitors;

[0064] 2) Using an electrochemical workstation, a cyclic voltammetry test was performed on the aluminum ion capacitor prepared in step 1). The results are as follows: Figure 2 shown.

[0065] Depend on Figure 2 It can be seen that the overlap rate of the cyclic voltammetry curves of the aluminum ion capacitor for three cycles is high, which shows that the N and S co-doped hollow carbon spheres have good reversibility and strong stability.

[0066] Test Example 3

[0067] Cyclic performance test

[0068] Test method:

[0069] 1) The N and S co-doped hollow carbon spheres prepared in Example 1 were used as positive electrodes and assembled with aluminum negative electrodes to form aluminum ion capacitors.

[0070] 2) The aluminum ion capacitor prepared in step 1) was subjected to a charge-discharge cycle test under the following test conditions: the charge-discharge current density was 1.0A g -1 , the charge and discharge cut-off voltage is 0.01~2.1V, the results are as follows Figure 3 shown.

[0071] Depend on Figure 3 It can be seen that in the voltage range of 0.01~2.1V, 1.0A g -1 At a current density of 1.34 W, the energy storage performance of the aluminum ion capacitor can reach 67 F g -1 After 3200 cycles, the capacity retention rate of the above aluminum ion capacitor is 82%.

[0072] Test Example 4

[0073] Rate performance test

[0074] Test method:

[0075] 1) The N and S co-doped hollow carbon spheres prepared in Example 1 were used as positive electrodes and assembled with commercially available aluminum negative electrodes into aluminum ion capacitors;

[0076] 2) The aluminum ion capacitor prepared in step 1) was subjected to a rate performance test under the following test conditions: the charge and discharge current densities were 0.2, 0.5, 1.0, 2.0, and 5.0 A g -1 , the results are as follows Figure 4 shown.

[0077] Depend on Figure 4 It can be seen that at 0.2, 0.5, 1.0, 2.0, 5.0A g -1 At the current density of 1.34, the above aluminum ion capacitors have 101.85, 59.12, 49.45, 43.76, and 38.08 F g -1 This shows that the above-mentioned aluminum ion capacitor has good rate performance.

[0078] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0079] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing N and S co-doped hollow carbon spheres, characterized in that: The following steps are involved: S1. Evenly mix ethanol, ammonia water and deionized water to obtain a mixed solution A; S2, adding tetraethyl orthosilicate, resorcinol, formaldehyde, thiourea and F127 to the mixed solution A prepared in S1 in sequence and mixing evenly to obtain a mixed solution B; S3, adding ethyl orthosilicate to the mixed solution B prepared in S2, stirring overnight to obtain a mixed solution C; S4, pouring the mixed solution C prepared in S3 into a reactor for hydrothermal reaction to obtain a N, S co-doped hollow carbon sphere precursor; S5. Place the N, S co-doped hollow carbon sphere precursor prepared by S4 in an inert gas and carbonize it at high temperature. Then, immerse the N, S co-doped hollow carbon sphere precursor after high temperature carbonization in a potassium hydroxide aqueous solution until SiO2 is completely removed to obtain N, S co-doped hollow carbon spheres.

2. The method for preparing N and S co-doped hollow carbon spheres according to claim 1, characterized in that: The volumes of the ethanol, the ammonia water and the deionized water in S1 are all 0 to 50 mL.

3. The method for preparing N and S co-doped hollow carbon spheres according to claim 1, characterized in that: The volumes of the ethyl orthosilicate and the formaldehyde in S2 are both 0-10 mL.

4. The method for preparing N and S co-doped hollow carbon spheres according to claim 1, characterized in that: The masses of the resorcinol, the thiourea and the F127 in S2 are all 0-5 g; the F127 is a polyoxyethylene-polyoxypropylene-polyoxyethylene block copolymer.

5. The method for preparing N and S co-doped hollow carbon spheres according to claim 1, characterized in that: The volume of the tetraethyl orthosilicate in S3 is 0 to 10 mL.

6. The method for preparing N and S co-doped hollow carbon spheres according to claim 1, characterized in that: The temperature required in the hydrothermal reaction process in S4 is 60°C to 300°C.

7. The method for preparing N and S co-doped hollow carbon spheres according to claim 1, characterized in that: The temperature of the high temperature carbonization in S5 is 400°C to 1200°C.

8. The method for preparing N and S co-doped hollow carbon spheres according to claim 1, characterized in that: The concentration of the potassium hydroxide aqueous solution in S5 is 1 mol L -1 .

9. A N, S co-doped hollow carbon sphere prepared by the preparation method as described in any one of claims 1 to 8.

10. A N, S co-doped hollow carbon sphere prepared by the preparation method according to any one of claims 1 to 8, used as a positive electrode material in an aluminum ion capacitor.

Citation Information

Patent Citations

  • Preparation method for nitrogen-doped nuclear shell hollow carbon

    CN104961121A

  • Hollow carbon sphere and preparation method and application thereof

    CN109824030A

  • Method for using N, S double-doped graphene as positive electrode of aluminum ion battery

    CN116598597A

  • Preparation method and application of nitrogen-sulfur co-doped resin-based hard carbon

    CN117125692A

  • Aluminum-ion capacitor and uses thereof

    US20170338052A1